Maternal and Child Health Habitus in Coastal Areas - Rahma Syafitri; Sri Wahyuni; Siti Arieta; Diof Hafiz (Indonesian Journal of Medical Anthropology, 2024)
This research explores the health habits of mothers and children in coastal communities. Habitus is interpreted as habits carried out by mothers and children to improve health status. This research uses a qualitative approach. The aim of collecting qualitative data is to explore the health habits of mothers and children in coastal communities, especially in the Dompak sub-district area. Qualitative data collection used in-depth interview procedures with officials and native housewives (not immigrants) on Dompak Island. The selection of informants was based on purposive sampling procedures, this was with the aim of exploring more deeply the research questions with native female informants on Dompak Island. This research contributes to the development of cross-disciplinary science in the social sciences, especially the science of health sociology regarding the health habits of mothers and children in coastal areas. This scientific contribution is theoretically useful when the results of this research are published in the form of scientific publications. This research is planned to be published in the reputable national journal Sinta. In addition to publication output, this research is expected to be an academic contribution as a recommendation for policy makers, especially in health policy, to understand community culture in the health sector so that they can take a more appropriate approach so that the goals of health policy are accepted by the community.